Near-ideal van der Waals rectifiers based on all-two-dimensional Schottky junctions - Xiankun Zhang (Nature Portfolio, 2021)
Here, a defect healing method is used to tune the height and width of the Schottky barrier at the interface between 2D metals and 2D semiconductors, leading to the realization of van der Waals rectifiers with enhanced performance.